ANALISIS PORTABILITAS INSTRUMEN PENGUKURAN SISTEM PEMERINTAHAN BERBASIS ELEKTRONIK (SPBE - Meylia Susiana Dewi Putri; Rudy A.G. Gultom; Achmad Farid Wadjidi (Jurnal Informatika Teknologi dan Sains (Jinteks), 2023)
Instrument portability is an important factor in determining whether a model or measurement system is simple to implement and, ultimately, related to the effectiveness and efficiency of resource use. The purpose of this study is to determine the portability of the SPBE digital measurement instrument. The research method used is a quantitative method with the help of XLSTAT software. This study used two analyses, namely readability analysis and outlier analysis. The results showed that the SPBE instrument was not portable, which was supported by an outlier result of 50.2% and an ease of reading score of 19.59.